Police Station, Vaals - Bart Lootsma (Oz, 1996)
Vaals is a small town at the southern tip of Holland, where the country meets Belgium and Germany. With its gently sloping hills, the fine landscape around here is very un-Dutch. (Ed. note: The project is by Wiel Arets Architects and Associates and text by Bart Lootsma.)